Serum homocysteine, vitamin B12 andzinc level in autism spectrum disorder children in Dhaka city - Naznin, Tahmina; Shahjadi, Shorifa; Shimul, Shanaz Khan (Journal of Bangladesh Society of Physiologist, 2025)
Background: Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder with genetic and enviromental etiology. Homocysteine (Hcy) is a non-protein á-amino acid, its overproduction could add to the pathophysiology associated with autism. Serum homocysteine metabolism is closely related with vitamin B12 and zinc level for proper enzymatic function. Objectives: To evaluate the serum homocysteine, vitamin B12 and zinc level in children with autism spectrum disorder. Methods: This cross-sectional observational study was conducted on 35 diagnosed ASD children enrolled from parent’s forum of autistic children, Mohakhali, Dhaka.Age BMI mached apparently healthy children were control. Serum homocysteine, vitamin B12 and zinc level were estimated by automated analyzer. For statistical analysis students unpaired “t” test was done. Results: The mean value of serum homocysteine was significantly higher whereas the Vitamin B12 and Zinc level were lower in ASD than the control group. Conclusion: ASD children are prone to have higher homocysteine with lowered vitamin B12 and zinc level. J Bangladesh Soc Physiol 2024;19(1): 29-34